2019
DOI: 10.1002/jssc.201800986
|View full text |Cite
|
Sign up to set email alerts
|

Screening and isolation of cyclooxygenase‐2 inhibitors from Trifolium pratense L. via ultrafiltration, enzyme‐immobilized magnetic beads, semi‐preparative high‐performance liquid chromatography and high‐speed counter‐current chromatography

Abstract: Nonsteroidal anti‐inflammatory drugs reportedly reduce the risk of developing cancer. One mechanism by which they reduce carcinogenesis involves the inhibition of the activity of cyclooxygenase‐2, an enzyme that is overexpressed in various cancer tissues. Its overexpression increases cell proliferation and inhibits apoptosis. However, selected cyclooxygenase‐2 inhibitors can also act through cyclooxygenase‐independent mechanisms. In this study, using ultrafiltration, enzyme‐immobilized magnetic beads, high‐per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…The mixture was then centrifuged at 10,000× g and 25 °C for 10 min with an ultrafiltration membrane (molecular weight cut-off, 100 kDa) to remove any unbound compounds. Thereafter, 100 μL MeOH: water mixture (50:50, v / v , pH 3.3) was added to the UF membrane and centrifuged at 10,000× g for 10 min (×3) to release the bound ligand [ 29 ]. The LDH inhibition rate was calculated using the equation (Aa−Ab)/Aa × 100%, where Aa and Ab are the absorbances of the blank and the experimental group, respectively [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The mixture was then centrifuged at 10,000× g and 25 °C for 10 min with an ultrafiltration membrane (molecular weight cut-off, 100 kDa) to remove any unbound compounds. Thereafter, 100 μL MeOH: water mixture (50:50, v / v , pH 3.3) was added to the UF membrane and centrifuged at 10,000× g for 10 min (×3) to release the bound ligand [ 29 ]. The LDH inhibition rate was calculated using the equation (Aa−Ab)/Aa × 100%, where Aa and Ab are the absorbances of the blank and the experimental group, respectively [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…MOL2 alleviated carbon tetrachloride-induced liver injury partly due to downregulate the expression of pro-inflammatory mediators, including PTGS2 [86]. MOL10 was identified as a PTGS2 inhibitor by using ultrafiltration, enzyme-immobilized magnetic beads, high-performance liquid chromatography, and electrospray-ionization mass spectrometry [87]. In addition, it was reported that MOL10 treatment significantly reduced the overexpression of PTGS2 mRNA [88].…”
Section: Discussionmentioning
confidence: 99%
“…HSCCC also has high recovery, high efficiency, and easy scale‐up potential. It is an excellent separation technique that has been widely used for the isolation and purification of active compounds from natural products [21].…”
Section: Introductionmentioning
confidence: 99%